Evidence for the importance of extracranial venous flow in patients with idiopathic intracranial hypertension (IIH) - Alperin, N; Lee, S H; Mazda, M; Hushek, S G; Roitberg, B; Goddwin, J; Lichtor, T (Acta neurochirurgica. Supplement, 2005)
Idiopathic intracranial hypertension (IIH) is characterized by increased ICP without evidence for intracranial mass lesion. Although the pathogenesis remains unknown, some association was found with intracranial venous thrombosis. To our knowledge, the extracranial venous drainage was not systematically evaluated in these patients. This study compared extracranial cerebral venous outflow in eight IIH patients and eight control subjects using magnetic resonance (MR) Venography and flow measurements. In addition, the study identified extracranial factors that affect cerebral venous drainage. In six of the IIH patients, either complete or partial functional obstruction of the internal jugular veins (IJVs) coupled with increased venous outflow through secondary venous channels was documented. On average, a four-fold increase in mean venous flow rate through the epidural and/or vertebral veins was measured in IIH patients compared with the healthy subjects. In one of the healthy subjects, intracranial venous outflow was studied also during external compression of the IJVs. Over 40% of the venous outflow through the IJVs shifted to the epidural veins and intracranial pressure, measured noninvasively by MRI, increased from 7.5 to 13 mmHg. Findings from this study suggest that increased ICP in some IIH patients could be associated with increased extracranial resistance to cerebral venous outflow.